RESPONSIBILITY OF POLITICAL PARTIES FOR VIOLATIONS OF THE PROCEDURE FOR THEIR FINANCING AND REPORTING IN UKRAINE AND THE EUROPEAN UNION MEMBER STATES - Zubenko, Hanna (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2025)
Introduction. The article is devoted to the study of the peculiarities of legal regulation of liability of political parties for violation of legislation on their financing and reporting. The purpose of the study is to reveal the problematic issues of legislative regulation and practical implementation of liability of political parties in Ukraine for violation of legislation on financing their activities and reporting on property, income, expenses and financial liabilities To achieve this goal, the author uses such methods of scientific research as logical and semantic, formal and legal, systemic and structural, comparative and legal, etc. Summary of the main research results. The article considers the European regional standards for financing political parties. On the basis of the analysis of the above-mentioned standards, the main principles of liability of political parties for violation of the procedure of such financing are highlighted. The experience of some EU member states regarding the liability of political parties for violations of legislation in the field of their financing and reporting is considered. The author focuses on the legislation of Ukraine providing for offences that may be committed in this sphere. Conclusions. The author emphasises the need to strengthen the responsibility of political parties for violations of the procedure for their financing and reporting, in particular for: non-compliance with restrictions on making contributions to support political parties; violation of the procedure for obtaining state funding for the statutory activities of a political party; violation of the procedure for submitting a report by a political party on property, income, expenses and financial liabilities.